Kewajiban Penggunaan Google Play Billing Yang Dilakukan Oleh Google LLC - Rocky Bial, Anandatama; Yahanan, Annalisa; Samawati, Putu (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Google, as the largest application platform, exploits its dominant position by requiring the use of Google Play Billing (GPB) for all digital transactions on Android. Through normative legal research based on literature, relevant regulations, and KPPU Decision No. 03/KPPU-I/2024, it was found that Google LLC had engaged in monopolistic practices. The KPPU ordered Google to open up alternative payment methods within applications through the User Choice Billing (UCB) programme, provide incentives for a minimum 5% reduction in service fees for one year, and impose a fine of IDR 202,500,000,000. This case underscores that the policies of large-scale digital companies must adhere to the principles of fair competition and highlights the importance of the KPPU's role in overseeing business practices in the digital economy era